The Fibrinolytic System in Patients with Right Ventricular Failure Treated with Novurit - Worowski, K; Gabryelewicz, A; Prokopowicz, J; Popławski, A (Thrombosis and Haemostasis, 1970)
It has been found that the activity of the fibrinolytic system is decreased in patients treated with Novurit. No changes were observed in patients treated with hydrochlorothiazide. Attention is drawn to the risk of administering organic mercurial diuretics to patients with a tendency toward hypercoagulability.